Legislative Legitimacy in Multicultural States: West Sumatra Province Law and Indigenous Peoples' Exclusion - Firdaus Arifin; Hardi Putra Wirman; Bagas Ihsanul Umam; Habibul Akhiar; Dea Maulvia Selfitri (Hakamain: Journal of Sharia and Law Studies, 2026)
This study examines the legislative legitimacy of Article 5 letter c of Law Number 17 of 2022 concerning West Sumatra Province following Constitutional Court Decision Number 97/PUU-XX/2022, focusing on whether the recognition of Minangkabau cultural identity through adat basandi syara’, syara’ basandi Kitabullah (ABS-SBK) reflects legitimate lawmaking while accommodating the recognition and participation of other Indigenous communities in a multicultural society. Employing an empirical juridical method, this study combines statutory, conceptual, comparative, and Islamic legal approaches with field research conducted in West Sumatra from January to April 2026. Primary data were collected through semi-structured interviews with Indigenous leaders, legislators, government officials, constitutional and Islamic law scholars, and civil society representatives, while secondary data included constitutional provisions, Law Number 17 of 2022, Constitutional Court decisions, legislative documents, Islamic legal literature, and international instruments concerning Indigenous Peoples’ rights. The findings reveal that the Constitutional Court affirmed the constitutionality of Article 5 letter c as a recognition of regional cultural identity; however, the provision continues to raise substantive legitimacy concerns due to limited accommodation of other Indigenous identities, particularly the Mentawai Indigenous Peoples. The study concludes that legislative legitimacy in multicultural states requires not only constitutional recognition but also meaningful participation, legal pluralism, and protection of diverse cultural identities. As an academic contribution, this research develops an analytical framework connecting Indigenous rights, multicultural constitutionalism, and Islamic legal values to strengthen inclusive lawmaking and contribute to international comparative constitutional scholarship.